(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
This paper explores the stages of organizing English lesson processes, focusing on key stages such as preparation, presentation, practice, and production. It highlights the importance of effective planning to ensure student engagement, skill development, and mastery of language concepts. The stages are examined in terms of their contribution to building a cohesive lesson structure that promotes active learning and critical thinking. Emphasis is placed on the teacher’s role in facilitating smooth transitions between stages and adapting to students’ needs. The study also discusses the integration of assessment and feedback throughout the lesson to enhance learning outcomes.